Different phenotypes of hypertension and associated cardiovascular and all-cause mortality: a systematic review and meta-analysis - Jay Tewari; Khalid Ahmad Qidwai; Shubhajeet Roy; Mehul Saxena; Anadika Rana; Ajoy Tewari; Vineeta Tewari; Anuj Maheshwari (The Egyptian Heart Journal)
Abstract Background Hypertension is a leading cause of premature mortality and morbidity. Recent guidelines advocate for out-of-office blood pressure monitoring, including ambulatory and home BP monitoring, to better identify hypertension phenotypes like masked hypertension, white coat hypertension, and sustained hypertension. However, clinical inertia persists due to a lack of robust evidence on the effectiveness of screening these phenotypes and their association with cardiovascular and all-cause mortality. This systematic review and meta-analysis aims to evaluate the relationship between various hypertension phenotypes and future cardiovascular events and all-cause mortality to support the broader implementation of out-of-office BP monitoring. Main body Following PRISMA, Cochrane, and MOOSE guidelines, we conducted a comprehensive search in Pubmed, OvidSP, and Cochrane Central databases up to October 17, 2023. Eligible studies reported associations between hypertension phenotypes and cardiovascular or all-cause mortality, with normotension as the reference group. Hazard ratios with 95% confidence intervals (CIs) were pooled using random-effects models. Eight studies with 15,327 participants were included. Masked hypertension was associated with increased cardiovascular mortality (pooled HR 2.05, 95% CI 1.69–2.48). Sustained hypertension also showed a higher risk (pooled HR 2.42, 95% CI 2.12–2.76). WCH did not significantly increase cardiovascular mortality risk (pooled HR 1.18, 95% CI 0.98–1.42). For all-cause mortality, neither masked hypertension (pooled HR 2.10, 95% CI 0.91–4.88) nor white coat hypertension (pooled HR 1.96, 95% CI 0.71–5.42) showed significant increases. Conclusion Masked hypertension and sustained hypertension are linked to higher cardiovascular mortality compared to normotension, highlighting the importance of out-of-office BP monitoring to identify and manage high-risk phenotypes effectively. Further high-quality studies are needed to generalize these findings and support policy changes.